THE EFFECTIVENESS OF INTERNET AS A REFERENCE SOURCE IN TERMS OF STUDENTS LEARNING OUTCOMES AND MIND MAPPING - Wita Setianingsih; Mundilarto Mundilarto (Universitas Negeri Yogyakarta, 2017)
This objective of the study is to find out the effectiveness of the Internet as a reference source for the classification of living things (1) in terms of students’ learning outcomes, (2) which was reviewed from the students’ mindmapping, (3) students’ learning outcomes dan students’ mindmapping. This was quasi-experimental study with the pretest-posttest control group design. The subject of this study was all of the grade VII students of SMP N 10 Yogyakarta. A sample of fifty-eight students grouped into two classes, namely class VII C and class VII D was established using the purpose sampling technique. The instruments used were a test to find out the students’ learning outcomes, observation sheets to reveal the students' ability in making a mind map, and the students’ response questionnaire to reveal the students’opinion on the internet and mind map. The hypothesis test used was T test and Hotelling`s T2 multivariat test (manova). The results of the study shows that the internet as a reference source on the classification of living things on the grade VII students of SMP N 10 Yogyakarta is effective which was shown by the attainment of absolute gain score results for the treatment group. The score is 10, 14 higher than the control group, and the achievement of a gain standard score for the treatment group is 0.2 higher than the control group. The Internet has not been effective which was shown by the percentage result of the lower treatment class achievement compared with the control class's achievements in terms of the students’ mindmapping. Both of them was shown F 8,118815 greater than P 3,16499